Hypoxia and laser enhance expression of SDF-1 in muscles cells - Mirahmadi, M; Ahmadiankia, N; Naderi-Meshkin, H; Heirani-Tabasi, A; Bidkhori, H R; Afsharian, P; Bahrami, A R (Cellular and Molecular Biology, 2016)
Targeted homing of transplanted mesenchymal stem cells (MSCs) is a decades old discussion in regenerative medicine. It has been proved that stromal cell-derived factor-1 (SDF-1Î±) is a potent chemoattractant of MSCs. Therefore, different strategies have been used to increase secretion of SDF-1Î± in damaged tissues to elevate targeted homing of MSCs. Previous studies have revealed that increased SDF-1Î± expression in hypoxic necrotic tissues and also low-level laser exposure enhanced angiogenesis in injured tissues. Herein, human skeletal and cardiac muscle cells (HSKM and HCM) were treated with hypoxia and low level laser to see their effects on expression of SDF-1Î± and on MSCs migration towards these treated cells. The optimal treatment conditions were determined by investigating the cellular viability after treatment. Real-Time PCR and Western blot analysis were done to study the expression of SDF-1Î± in treated cells. Migration potential of MSCs toward hypoxic and laser treated cells was investigated via migration assay. MTT assay revealed that laser and hypoxia treatment had no effect on the viability of HCM, HSKM compared with Glioblastoma cells. Real-Time PCR showed 16- and 90-fold elevation in mRNA of SDF-1Î± in HSKM and HCM cells, respectively, in laser treated with 12 J/cm2 intensity. In these two groups, selected as optimal conditions, HIF-1Î± expression showed maximum fold changes that might be partly because of response to treatments help to SDF-1Î± expression. It can be concluded that hypoxia and laser treatments may recruit MSCs and applied as a useful strategy for the further targeted stem cell homing.